2020
DOI: 10.3390/su12030790
|View full text |Cite
|
Sign up to set email alerts
|

Too Old for Recreation? How Friendly Are Urban Parks for Elderly People?

Abstract: Urbanization and ageing are the two main processes currently shaping the social environment worldwide. In this context, creating senior friendly cities should be an important target, especially in developed countries, which have the highest rates of population over 60 years old. Our study focuses on the use of urban parks and aims to analyze how friendly their planning, design, and use are for elderly people. We used field observation carried out in four case study parks in Bucharest (Romania) to assess the sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 36 publications
3
31
0
1
Order By: Relevance
“…Age: In both genders, especially women, increasing age contributed to a higher CN, which is in line with other studies [8,10,48,51]. According to the literature, the higher CN in older individuals is linked to a higher number of visits to natural spaces [52] and to greater opportunities for engaging with them [53]. Older people develop deeper connections with their surroundings, attaching greater meaning to the little things in life [54].…”
Section: Connectedness To Nature and Demographic Variablessupporting
confidence: 86%
“…Age: In both genders, especially women, increasing age contributed to a higher CN, which is in line with other studies [8,10,48,51]. According to the literature, the higher CN in older individuals is linked to a higher number of visits to natural spaces [52] and to greater opportunities for engaging with them [53]. Older people develop deeper connections with their surroundings, attaching greater meaning to the little things in life [54].…”
Section: Connectedness To Nature and Demographic Variablessupporting
confidence: 86%
“…They express different needs and preferences, especially when looking at the particular features of the components of GI (Ives et al 2017 ), although recurring and cross-cutting preferences in green spaces can be identified (Henneberry et al 2020 ). For example, the study by Onose et al ( 2020 ) showed that the needs and preferences of elderly people can vary greatly from the ones of other social groups. GI should be designed to provide equitable access and diversified facilities to all users.…”
Section: How Should Green Infrastructure Be Expanded and Improved?mentioning
confidence: 99%
“…This study describes a complex model of the frequency of visiting parks, observed during the COVID-19 pandemic in Bucharest. We started from a base level in January and February where there is a reduced frequency of visits in green areas, due mainly to the weather and the shorter daytime as explained in other studies [16]. Since the end of March, a state of emergency has been installed in Romania, leading to a decline in the frequency of visiting parks.…”
Section: Discussionmentioning
confidence: 99%
“…Although they make a major contribution to the day-to-day activities, most parks do not serve everyone in the community equally [15]. Visitor typologies are differentiated by age, gender, education, lifestyle, health or mobility capacity [16]. People use parks for different activities, both personal and professional.…”
Section: Introductionmentioning
confidence: 99%